Increased Understanding of The First Handling of Sports Injuries in PJOK Teachers in Lakarsantri District, Surabaya - Nurpratiwi, Resti; Triardhana, Yanuar Alfan; Ciptorini, Ariesia Dewi; Lestari, Bhekti; Suyoko, Andri; Sidik, Muhammad Asrul (Journal of Sport Moovera (JSM), 2023)
Community service activities about the importance of understanding the first handling of sports injuries to PJOK Teachers in Lakarsantri District, Surabaya have the aim of increasing the understanding of PJOK teachers in providing appropriate and fast first treatment of sports injuries to be able to speed up the recovery process. The method applied uses offline socialization regarding the first treatment of sports injuries with power point aids and learning modules. The community service team uses projectors, laptops, mics, socialization materials and documentation tools as tools and materials. The first socialization material explains the first handling of sports injuries. In this first material, it explains about sports injuries in soft tissues and methods of handling them using the PRICE method. On the second material about cramps. The second material explains about cramps, their causes and treatment. The output of this activity is the ability of PJOK teachers to provide the first treatment of sports injuries to students so that they can speed up the recovery period.